Sketch-based 3D modeling and reconstruction - Wang, Kai. (2013)
This research investigates the use of sketching techniques in 3D modeling and reconstruction to enhance various processes such as 3D model creation, editing, analyzing and computing. 3D geometric models have been widely used in various applications from industrial design to digital entertainment. However, creating and processing 3D models with traditional 2D WIMP-style (Windows, Icon, Menu, Pointer) interfaces are generally tedious and time-consuming. On the other hand, sketching interfaces are emerging as a new approach to enhance user interactions for various design activities. The sketching interfaces are expected to provide flexible and intuitive interactions between computers and users. To effectively incorporated the sketching techniques into 3D modeling and reconstruction, some fundamental theories and supporting algorithms should be developed. The goal of this research is thus to investigate how to create intuitive and effective sketching interfaces and meanwhile to develop sketch-based techniques for creating and editing 3D geometric models. Firstly, we develop a reference plane assisted sketching interface for freeform shape design, in which users can create and edit 3D models through simple sketches. To regularize and interpret the user input properly when sketching the shape of the 3D object, we introduce some rules for the strokes into the system, which consider both the semantic meaning of the sketched strokes and human psychology. To make 3D location and orientation of strokes meaningful and intuitive within 2D interface, we propose to perform the modeling operations with reference to some auxiliary planes, which are automatically constructed based on the user sketches or default setting. The use of reference planes helps to make the sketch-based modeling system more intuitive and easy to use.